2020
DOI: 10.21203/rs.3.rs-16022/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Therapeutic Efficacy of Adjunct Therapeutic Plasma Exchange for Septic Shock with Multiple Organ Failure: A Single Center Retrospective Review

Abstract: Background: Sepsis remains a common condition with high mortality when multiple organ failure develops. The evidence for therapeutic plasma exchange (TPE) in this setting is promising but inconclusive. Our study aims to evaluate the efficacy of adjunct TPE for septic shock with multiple organ failure compared to standard therapy alone. Methods: A retrospective, observational chart review was performed, evaluating outcomes of patients with catecholamine resistant septic shock and multiple organ failure in Inten… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Our group has developed institutional guidelines for TPE consideration in sepsis with multiple organ dysfunction syndrome (MODS) (from any pathogen), and recently completed a retrospective review of our single-center experience in this setting. 11 Details are available online, and a revised version of the article will be submitted for publication. In our study, nearly half the patients presented with pneumonia as the primary source of infection (39/80).…”
Section: Discussionmentioning
confidence: 99%
“…Our group has developed institutional guidelines for TPE consideration in sepsis with multiple organ dysfunction syndrome (MODS) (from any pathogen), and recently completed a retrospective review of our single-center experience in this setting. 11 Details are available online, and a revised version of the article will be submitted for publication. In our study, nearly half the patients presented with pneumonia as the primary source of infection (39/80).…”
Section: Discussionmentioning
confidence: 99%
“…Prior experience in patients with acute lung injury due to the 2009 pH1N1 influenza A virus showed improvement in hemodynamic status and PaO2/FiO2 ratio after TPE [185]. Another retrospective observational study showed improvement in adjunctive use of TPE in patients with septic shock due to pneumonia [186]. Due to the limited evidence, TPE should be further investigated regarding a possible role in treatment of COVID-19-CSS, ideally in randomized clinical trials.…”
Section: Plasma Exchangementioning
confidence: 99%
“…An unpublished retrospective observational study comparing 40 patients with COVID‐19 complicated by MOF and septic shock who received adjunct TPE with 40 propensity matched controls who received supportive care without TPE found no difference in PaO2/FiO2 (P/F) ratio between the two groups at 48 h after TPE ( P = .84). After subgroup analysis, the 28‐day mortality benefit (47.8% vs 81.3%; P = .05) may be present for patients with pneumonia as the primary source of sepsis treated with TPE 47 …”
Section: Covid‐19 and Therapeutic Plasma Exchangementioning
confidence: 97%
“…Therapeutic plasma exchange has additionally been used to treat severe COVID‐19 with ARDS accompanied by MOF and/or septic shock 23,43‐47 . Keith et al 43 reported a single patient experience with COVID‐19 positive pneumonia who developed MOF and septic shock requiring cardioversion and mechanical ventilation.…”
Section: Covid‐19 and Therapeutic Plasma Exchangementioning
confidence: 99%